2014
DOI: 10.1186/s13068-014-0171-1
|View full text |Cite
|
Sign up to set email alerts
|

System-level network analysis of nitrogen starvation and recovery in Chlamydomonas reinhardtii reveals potential new targets for increased lipid accumulation

Abstract: BackgroundNitrogen starvation is known to cause drastic alterations in physiology and metabolism leading to the accumulation of lipid bodies in many microalgae, and it thus presents an important alternative for biofuel production. However, despite the importance of this process, the molecular mechanisms that mediate the metabolic remodeling induced by N starvation and especially by stress recovery are still poorly understood, and new candidates for bioengineering are needed to make this process useful for biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 94 publications
9
159
0
9
Order By: Relevance
“…Although the effects on carotenoid biosynthesis and secondary metabolism following TORC1 inhibition required 8 h to become detectable, this is the first evidence that carotenoid production is modulated by TOR signaling in algae. Additionally, altered cyclase protein levels are not likely responsible for this finding because previous studies showed no change in lycopene beta/epsilon cyclase protein level after up to 24 h of nitrogen stress (Cunningham & Gantt, ; Valledor et al ., ), a condition that is metabolically similar to TOR inhibition (Perez‐Perez et al ., ; Roustan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects on carotenoid biosynthesis and secondary metabolism following TORC1 inhibition required 8 h to become detectable, this is the first evidence that carotenoid production is modulated by TOR signaling in algae. Additionally, altered cyclase protein levels are not likely responsible for this finding because previous studies showed no change in lycopene beta/epsilon cyclase protein level after up to 24 h of nitrogen stress (Cunningham & Gantt, ; Valledor et al ., ), a condition that is metabolically similar to TOR inhibition (Perez‐Perez et al ., ; Roustan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…10). The behavior of ADHE and PFL in response to N-starvation is interesting because it contrasts with that of other chloroplast proteins, including enzymes of the Calvin-Benson-Bassham (CBB) cycle and components of the photosynthetic chain, whose levels decreased shortly after the transfer to N-free medium (40,41). Here we observed within the first 24 h of N-starvation an important decrease (more than 50%) in the abundance of RBCL and phosphoribulokinase, two key enzymes of the CBB cycle, and of ADP-glucose pyrophosphorylase (ADPG; EC 2.7.7.27), the chloroplast enzyme that catalyzes the first committed step in starch synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Black boxes denote pathway names. A recently proposed C4-like carbon-concentrating mechanism (CCM) in microalgae78798081 is shown to depict an alternative route for carbon assimilation. Neutral lipid droplets found in microalgae consist mostly of triacylglycerols (TAGs), formed by combining FAs and glycerol.…”
Section: Figurementioning
confidence: 99%